PERAN SEKOLAH LUAR BIASA PELITA HATI DALAM MENANGANI ANAK TUNAGRAHITA DI KOTA PEKANBARU - Fani Aulia Rizki; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at the Special School Pelita Hati Pekanbaru. This study aims to determine the role of Pelita Hati School in dealing with children with intellectual challenges and to find out the school-parent cooperation in dealing with children with intellectual challenges. This study, entitled “The Role of Special School Pelita Hati Handling Mentally Retarded Children in the City of Pekanbaru”. Quite fathomable this research subject is how the role of Pelita Hati School in dealing with children with intellectual challenges and any cooperation undertaken and obstacles in dealing with children with intellectual challenges. The samples in this research is purposive technique. Total sample of 10 people and key informants 1. The method used is a qualitative descriptive method with qualitative data analysis. Instrument data filtering is observation, interview and documentation. Results of general research conducted, the researchers conclude: the role of Pelita Hati School in dealing with children with intellectual challenges fundamental form of giving lessons and to identify and hone the skills of the students. Cooperation between the school and parents in dealing with children with intellectual challenges in the form of exchanging ideas and information about the child’s development. Natural barriers in retarded child is 4, is difficulty in learning problems, problems of adjustment, speech and language disorders, and personality problems. Solutions to overcome barriers retarded child my be providing appropriate learning and create a proper learning environment.Keywords: Role, Special School, Tunagrahita